2022
DOI: 10.3389/fmed.2022.869372
|View full text |Cite
|
Sign up to set email alerts
|

A Toolbox to Investigate the Impact of Impaired Oxygen Delivery in Experimental Disease Models

Abstract: Impaired oxygen utilization is the underlying pathophysiological process in different shock states. Clinically most important are septic and hemorrhagic shock, which comprise more than 75% of all clinical cases of shock. Both forms lead to severe dysfunction of the microcirculation and the mitochondria that can cause or further aggravate tissue damage and inflammation. However, the detailed mechanisms of acute and long-term effects of impaired oxygen utilization are still elusive. Importantly, a defective oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 203 publications
(213 reference statements)
0
4
0
Order By: Relevance
“…However, medical treatment relied on indirect variables to monitor microvascular oxygen delivery, tissue perfusion and cell integrity. Therefore, the invention and development of devices thought to investigate microcirculation directly were a cornerstone of modern intensive care research 23 . Trzeciak et al reported an improvement of microvascular flow in septic patients to be associated with a decrease in multi-organ failure after 24 h despite the registration of similar macrocirculatory variables 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, medical treatment relied on indirect variables to monitor microvascular oxygen delivery, tissue perfusion and cell integrity. Therefore, the invention and development of devices thought to investigate microcirculation directly were a cornerstone of modern intensive care research 23 . Trzeciak et al reported an improvement of microvascular flow in septic patients to be associated with a decrease in multi-organ failure after 24 h despite the registration of similar macrocirculatory variables 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Those findings are in accordance with previous observations from our working group 28 . Finally, perfusion markers are reproducibly capable for microvascular monitoring in hemorrhagic sheep, dogs and rats and independent of the modus of shock induction 23 . In 2018 an expert group from the Cardiovascular Dynamics Section of the European Society of Intensive Care Medicine published a second consensus paper with recommendation how to evaluate the microcirculation in critically ill patients 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, continuous drug infusion was started. After thirty minutes of observation, a fixed-volume hemorrhage was inducted by removing 20% of the estimated total blood volume within 5 min duration via an intravenous peripheral cannula and the arterial catheter ( 40 ). According to Advanced Trauma Life Support (ATLS) shock classification, this represents a class II shock ( 41 ).…”
Section: Methodsmentioning
confidence: 99%